A method to achieve spectral beam combining based on a novel symmetric grating - Fan, Xinmin; Zhang, Jianxin; Li, Sensen; Li, Shun; Wang, Yan; Du, Fei; Huang, Xiaodong; Li, Yingde; Zhang, Lujun; Wang, Chunyan (Frontiers in Physics, 2022)
A symmetric grating is proposed to obtain higher output power in spectral beam combination by increasing the number of lasers and spectral utilization. The grating allows laser beams to be incident from both sides of the grating normal to achieve coaxial beam combining, so the number of beams and the combined output power are doubled compared with the traditional grating under the same spectral line-width. The grating is designed with the central wavelength of 4.65 μm, and the calculation results show that this grating is very advantageous for spectral beam combining, especially for the light waves in the range 4.55–4.71 μm, where their diffraction efficiencies are high (over 80%) and correspond to a wide and linear range of incidence angles. Meanwhile, based on the symmetric gratings we further propose a circular grating to achieve the same frequency spectral beam combining. This beam combining design will not increase the laser spectral line width while enhancing the laser power, reducing the requirements for the unit laser spectral line width, which is very meaningful in some application fields and will further enrich the research of spectral beam combining.